THE DEVELOPMENT OF LEARNING ACHIEVEMENTS ON TYPES AND FUNCTIONS OF WORDS IN SENTENCES OF GRADE 6 STUDENTS BY USING INQUIRY PROCESS MODEL - Juraya, Phimthida; Prommuang, Pinyo (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The purpose of this study was 1) to compare the development of academic achievement about words and functions of words in sentences of the grade 6 students by using the Inquiry-Based Instructional Model, 2) to compare the development of academic achievement posttest scores with the criteria of 70 percent. The sample group consisted of 15 students in grade 6/1 students at Anusarn Wittaya School, Pak Thong Chai District, Nakhonratchasima Province, in Semester 2 Academic Year 2021. Research instruments consisted of lesson plan and learning achievement test. Statistics used to analyze data include: frequency, percentage, average, standard deviation, and Wilcoxon Matched Pairs Sign Rank Test. The research results were as follows: 1) Learning achievement on Words and Functions of Words in Sentences of grade 6 students using Inquiry-Based Instructional Model was 6.47 or 21.56 percent for pretest scores, and was 22.40 scores of posttest or 74.67%. Their progression scores were of 15.93 points or 53.11%. 2) Comparing their learning achievement posttest scores on Words and Functions of Words in Sentences of grade 6 students using Inquiry-Based Instructional Model had not more statically significant than the criteria of 70%.